Integration of Conventional Counseling Within Islamic Counseling Practices In Islamic Boarding Schools In North Sumatra - Akhyar Lubis, Saiful; Zainun, Zainun; Putra Dinata Saragi , Muhammad; Nasution, Helsa; Amalia Azzahra Lubis, Adina (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This study attempts to ascertain how Islamic counseling is implemented at Islamic boarding schools in North Sumatra in comparison to conventional counseling. Qualitative descriptive research is what this study is. Interviews and observation are the methods utilized to obtain data. The respondents in this study are BK teachers in Islamic boarding schools located in North Sumatra. Specifically, the respondents are BK teachers employed by the Medan Islamic Center Foundation, Al-Khoir Islamic Boarding School, Darul Mursyid Islamic Boarding School, and Muhammadiyah Kwala Madu Islamic Boarding School. The findings of this study show that: (1) Guidance and counseling have been implemented in Islamic boarding schools in North Sumatra; BK teachers with counseling and guidance certifications have carried out programs and services that have been planned in accordance with field needs; individual and group counseling has been implemented the most frequently. Every Islamic boarding school has a unique emphasis that is modified to meet the requirements of the pupils. In order to create programs and field learning plans, the BK teachers assessed the needs of their pupils using a Problem Revealing Tool (AUM) and a questionnaire that was given to them. (2) The moral growth of pupils is the main goal of the application of Islamic guidance and counseling in North Sumatra's Islamic boarding schools. The services offered by BK teachers are designed to strengthen and instill religious teachings in students, drawing inspiration from the Al-Quran and Hadith. By incorporating religious beliefs into the counseling process, BK teachers use the Islamic counseling approach of